Studi Kasus Tentang Latar Belakang Anggota Keluarga Yang Melakukan Bunuh Diri Di Desa Tawaang Kecamatan Tenga Kabupaten Minahasa Selatan - Jesica Noviyanti Dalope; Deetje J Solang; Meike E Hartati (Riviera Publishing, 2025)
This study aims to analyze the family background of suicide victims in Tawaang Village by examining five key aspects: parenting style, educational background, social interaction, culture, and economic condition. This research employed a qualitative approach using in-depth interviews, observations, and data collection from informants such as the spouse, children, grandparents, pastors, village leaders, neighbors, and community elders. The findings reveal that parenting styles, whether democratic or authoritarian, do not necessarily prevent suicide risk when emotional support is inadequate. Low educational attainment limits understanding of mental health and coping skills. In terms of social interaction, both openness and limited engagement can serve as risk factors if not supported by quality emotional bonds. Cultural practices that once stigmatized suicide have shifted through the role of the church in providing spiritual support, although remnants of stigma persist. Furthermore, both “sufficient” and “limited” economic conditions may generate significant psychological distress. Overall, suicide in Tawaang Village is the result of a complex interplay between family, educational, social, cultural, and economic factors. This study highlights the importance of a holistic approach to suicide prevention, involving families, communities, and religious institutions.